α-Cyperone Attenuates H2O2-Induced Oxidative Stress and Apoptosis in SH-SY5Y Cells via Activation of Nrf2 - Huang, Bingxu; Liu, Juxiong; Fu, Shoupeng; Zhang, Yufei; Li, Yuhang; He, Dewei; Ran, Xin; Yan, Xuan; Du, Jian; Meng, Tianyu; Gao, Xiyu; Liu, Dianfeng (Frontiers in Pharmacology, 2020)
α-cyperone, extracted from Cyperus rotundus, has been reported to inhibit microglia-mediated neuroinflammation. Oxidative stress and apoptosis play crucial roles in the course of Parkinson's disease (PD). PD is a common neurodegenerative disease characterized by selective death of dopaminergic neurons. This study was designed to investigate the neuroprotective effects of α-cyperone against hydrogen peroxide (H2O2)-induced oxidative stress and apoptosis in dopaminergic neuronal SH-SY5Y cells. Neurotoxicity was assessed by MTT assay and measurement of lactic dehydrogenase (LDH) release. The level of reactive oxygen species (ROS) was measured by dichlorodihydrofluorescin diacetate (DCFH-DA) staining. The apoptosis of SH-SY5Y cells was evaluated by annexin-V-FITC staining. The translocation of NF-E2-related factor 2 (Nrf2) was determined by western blot and immunofluorescence staining. Western blot analysis was conducted to determine the expression level of cleaved-caspase-3, the pro-apoptotic factor Bax, and the anti-apoptotic factor, Bcl-2. The results showed that α-cyperone substantially decreased H2O2-induced death, release of LDH, and production of ROS in SH-SY5Y cells. In addition, we found that α-cyperone attenuated H2O2-induced cellular apoptosis. Moreover, α-cyperone remarkably reduced the expression of cleaved-caspase-3 and Bax, and upregulated Bcl-2. Furthermore, α-cyperone enhanced the nuclear translocation of Nrf2. Pretreatment with brusatol (BT, an Nrf2 inhibitor) attenuated α-cyperone-mediated suppression of ROS, cleaved-caspase-3, and Bax, as well as α-cyperone-induced Bcl-2 upregulation in H2O2-treated SH-SY5Y cells. α-cyperone neuroprotection required Nrf2 activation. In conclusion, α-cyperone attenuated H2O2-induced oxidative stress and apoptosis in SH-SY5Y cells via the activation of Nrf2, suggesting the potential of this compound in the prevention and treatment of PD.